The Responsibility Of Land Office On Landfarm Functional Shift To Housing - Tanazza Zalsabella Firsty; Imam Koeswahyono; Rachmad Safa'at (Faculty of Law, University of Mataram, 2019)
Regarding the transfer of agricultural land to housing, the reduction in the area of agricultural land in Blitar City is due to land conversion functions such as the construction of housing and other public facilities that are not in accordance with article 3 paragraph (1) letter g PERDA of the Blitar City Spatial Plan. In fact, regulations with reality that occur in the field are not in accordance with applicable regulations. The facts that occur on the ground are agricultural land being converted into housing that causing agricultural land to decrease. Based on this, the author made this study with the aim of analyzing the implementation of policies and accountability of the Blitar City Land Office for the conversion of agricultural land for housing in Blitar City.The research method used by the author is juridical empirical with a legal sociology approach. From the results of this study, it can be concluded that there is a lack of firmness in law enforcement towards the conversion of agricultural land which is still quite widely found in buildings in the form of housing and land converted to other non-agricultural land and not licensed. The results of the study show that there is a need for coordination between the City Government as a policy maker and agencies related to the conversion of agricultural land for housing, so that integrated supervision can be carried out so that changes in land use can be known earlier so that agricultural land does not decrease every year.